Role of cell adhesion molecule DM-GRASP in growth and orientation of retinal ganglion cell axons - Avci, Hasan; Zelina, Pavol; Thelen, Karsten; Pollerberg, G. Elizabeth (Developmental biology, 2004)
The cell adhesion molecule (CAM) DM-GRASP was investigated with respect to a role for axonal growth and navigation in the developing visual system. Expression analysis reveals that DM-GRASP's presence is highly spatiotemporally regulated in the chick embryo retina. It is restricted to the optic fiber layer (OFL) and shows an expression maximum in a phase when the highest number of retinal ganglion cell (RGC) axons extend. In the developing retina, axons grow between the DM-GRASP-displaying OFL and the Laminin-rich basal lamina. We show that DM-GRASP enhances RGC axon extension and growth cone size on Laminin substrate in vitro. Preference assays reveal that DM-GRASP-containing lanes guide RGC axons, partially depending on NgCAM in the axonal membrane. Inhibition of DM-GRASP in organ-cultured eyes perturbs orientation of RGC axons at the optic fissure. Instead of leaving the retina, RGC axons cross the optic fissure and grow onto the opposite side of the retina. RGC axon extension per se and navigation from the peripheral retina towards the optic fissure, however, is not affected. Our results demonstrate a role of DM-GRASP for axonal pathfinding in an early phase of the formation of the higher vertebrate central nervous system.